A deprotection strategy of a BODIPY conjugated porous polymer to obtain a heterogeneous (dipyrrin)(bipyridine)ruthenium(ii) visible light photocatalyst. Issue 44 (31st October 2016) - Liras, Marta; Pintado-Sierra, Mercedes; Iglesias, Marta; Sánchez, Félix
Abstract : A deprotection strategy of BODIPY conjugated porous polymers (CMPBDP) has been applied to synthesize a new (dipyrrin)(bipyridine)Ru(ii ) (CMPBDP-Ru ) efficient heterogeneous photocatalyst for iminium ion generation under visible light. Abstract : This work shows that a deprotection strategy of BODIPY conjugated porous polymers (CMPBDPs) can be successfully applied to synthesize a new (dipyrrin)(bipyridine)Ru(ii ) (CMPBDP-Ru ) efficient heterogeneous photocatalyst for iminium ion generation under visible light.CMPBDP-Ru shows high thermal and photochemical stability under irradiation, and it could be reused several times.